2014
DOI: 10.1007/s10201-014-0443-2
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the impact of flooding events on non-point source pollution and the effects of filter strips in an intensive agricultural watershed in China

Abstract: Non-point source pollution (NPSP) has become a critical pollution source after many improvements in point source pollution treatment have been made, particularly in China, due to intensive agricultural activities. Moreover, the impact of NPSP on surface water quality is significantly affected by extreme events, such as flooding. In this study, the soil and water assessment tool model was used to characterize the behaviours of NPSPs and to evaluate the effect of filter strips during flooding periods. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In addition, a high quantity of rainfall and humidity can cause loss of nutrients overflowing [62]. For more accurate precision of tree biomass prediction, incorporating different stand levels of the tree and climate variables could be better [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a high quantity of rainfall and humidity can cause loss of nutrients overflowing [62]. For more accurate precision of tree biomass prediction, incorporating different stand levels of the tree and climate variables could be better [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…The spatial analysis indicated that the impact of the high-intensive rainfall on the downstream (from Ganguyi to Tanjiahe) was great due to the confluence of the river tributaries in 2013, suggesting the severe threat of flooding events to the aquatic environment. It has been recognized that pollutant fluxes were very large during an extreme year because the pollutants temporarily stored in channels or slope lands are quickly entrained and transferred during floods (Chen et al 2015b). For example, the average value of COD was 155,683 kg/day at Ganguyi during 2013, which is nearly 9 times the average load (18,211 kg/day) across other years.…”
Section: Implications Of the Flood-pollution Loads Relationshipmentioning
confidence: 99%
“…The spatial analysis indicated that the impact of the high-intensive rainfall on the downstream (from Ganguyi to Tanjiahe) was great due to the confluence of the river tributaries in 2013, suggesting the severe threat of flooding events to the aquatic environment. It has been recognized that pollutant fluxes were very large during an extreme year because the pollutants temporarily stored in channels or slope lands are quickly entrained and transferred during floods (Chen et al, 2015b). For example, the average value of COD was 155,683 kg/d at Ganguyi during 2013, which is nearly 9 times the average load (18,211 kg/d) across other years.…”
Section: Implications Of the Flood-pollution Loads Relationshipmentioning
confidence: 99%